2019
DOI: 10.1039/c9ja00122k
|View full text |Cite
|
Sign up to set email alerts
|

Indium concentration fluctuations in InGaN/GaN quantum wells

Abstract: Secondary ion mass spectrometry measurements can provide specific information on In fluctuations in InGaN quantum wells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Finally, an important observation concerns the difficulty of growing InGaN layers with a homogeneous indium concentration [ 79 ] : this could lead to fluctuations in the indium molar content within the QW, thus altering the ideal charge distribution and the peak emission wavelength. [ 80 ]…”
Section: Defects In Gan Ledsmentioning
confidence: 99%
“…Finally, an important observation concerns the difficulty of growing InGaN layers with a homogeneous indium concentration [ 79 ] : this could lead to fluctuations in the indium molar content within the QW, thus altering the ideal charge distribution and the peak emission wavelength. [ 80 ]…”
Section: Defects In Gan Ledsmentioning
confidence: 99%
“…Igarashi reported the rst Pu isotope measurements in radioactive particles released during the accident to determine whether nuclear fuel radionuclides were present. 210 Radioactive particles from units 1, 2 and 3 were measured using ICP-MS, with Pu only detected in unit 1 materials at activities of 1.70-7.06 Â 10 À5 Bq for 239+240 Pu and 4.10-8.10 Â 10 À3 Bq for 241 Pu, with atom ratios consistent with ORIGEN (a computer code system for calculating the build-up, decay, and processing of radioactive materials) calculations and environmental measurements. The difference in results between samples showed the value in measuring Pu isotopes for monitoring particle formation processes.…”
Section: Nuclear Materialsmentioning
confidence: 83%
“…Eppich et al focused on Pu isotopes in environmental swipe samples measured using MC-ICP-MS following digestion and chemical separation. 203 The method was validated using reference materials, with a precision of <1% achieved for 240 Pu/ 239 Pu, 241 Pu/ 239 Pu and 242 Pu/ 239 Pu at a ratio of $6.3 Â 10 À2 . A 239 Pu detection limit of 0.10-0.58 fg was calculated, with an expanded uncertainty averaging 1.7% in swipe samples containing 0.32 fg and 10.5 fg total Pu.…”
Section: Nuclear Materialsmentioning
confidence: 99%
“…In-depth studies of atom probe tomography have provided valuable insights on the In distribution in the InGaN QWs [31][32][33][34][35][36] . Extensive atomically-resolved characterization techniques, such as scanning transmission electron microscopy (STEM) [37][38][39][40][41] have proved the absence of large scale (on the order of tens of nanometers) compositional fluctuations. Nevertheless, atomistic-scale investigations using high-resolution electron microscopy suffer from a limited field of view, which hinders the detection of accurate size distribution of potential compositional fluctuations [37][38][39][40][41] , and possible beam-induced structural modifications 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive atomically-resolved characterization techniques, such as scanning transmission electron microscopy (STEM) [37][38][39][40][41] have proved the absence of large scale (on the order of tens of nanometers) compositional fluctuations. Nevertheless, atomistic-scale investigations using high-resolution electron microscopy suffer from a limited field of view, which hinders the detection of accurate size distribution of potential compositional fluctuations [37][38][39][40][41] , and possible beam-induced structural modifications 42 . Recently, it has been shown that imaging under the knock-on threshold preserves the QW structures 38,43 , allowing the quantification of compositional fluctuations at the sub-nanometer scale.…”
Section: Introductionmentioning
confidence: 99%